2004
DOI: 10.1308/003588404322827455
|View full text |Cite
|
Sign up to set email alerts
|

Resource and manpower calculations for the provision of hepatobiliary surgical services in the UK

Abstract: G astrointestinal surgery in the UK is increasingly becoming sub-specialised into upper and lower gastrointestinal surgery with the management of patients being based on a multidisciplinary team approach. Upper gastrointestinal surgery is further divided into hepatopancreato-biliary surgery (HPB) and oesophago-gastric surgery.1 Most upper gastrointestinal surgeons treat patients with benign conditions affecting all these organs, but malignant conditions of the liver, bile duct and pancreas are increasingly dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…The growing utilization of hepatobiliary surgical procedures in a more obese patient population demands that surgeons recognize the complex relationship between obesity and surgical outcomes 811. Several single center studies have demonstrated that obesity has specific implications on the health of the liver, but our understanding of how obesity affects multi-system complications is limited by descriptions with modest sample size 1214.…”
Section: Introductionmentioning
confidence: 99%
“…The growing utilization of hepatobiliary surgical procedures in a more obese patient population demands that surgeons recognize the complex relationship between obesity and surgical outcomes 811. Several single center studies have demonstrated that obesity has specific implications on the health of the liver, but our understanding of how obesity affects multi-system complications is limited by descriptions with modest sample size 1214.…”
Section: Introductionmentioning
confidence: 99%
“…11 Hepatobiliary surgical expertise has become confined to these centres, which in turn are fed by a group of smaller regional hospitals, forming individual cancer 'networks'. This is the case in the North Trent Cancer Network, where Sheffield Teaching Hospitals NHS Trust provides liver and pancreatic surgical services to Sheffield itself and a group of four district hospitals (Fig.…”
mentioning
confidence: 99%
“…However, even if one assumes that all metastatic liver disease presentations among patients treated with liver resection surgery did relate to metastatic disease from colorectal primaries, this would have meant that the liver resection activity actually observed for colorectal liver metastases was about half the previously theoretically predicted population rate levels, i.e. 3.9/100 0000 8 .…”
Section: Discussionmentioning
confidence: 99%
“…It could therefore be postulated that diffusion of liver resection surgery might have been slow, and that provision of this type of surgery may have been below the healthcare need levels that could be theoretically expected. A previous study from an English liver surgery unit has indicated a theoretical healthcare need of approximately 3.9 liver resection surgery episodes for metastatic disease of the liver from colorectal primaries per 100 000 general population 8 . However, this evidence relates to only one study and research setting and to metastatic liver disease from colorectal primaries alone, i.e.…”
Section: Introductionmentioning
confidence: 99%